How Women Experience and Evaluate Midwifery-Led Care During Childbirth: Insights from a Mixed-Method Study - Rashash, Doaa Sami (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Midwifery-led care has been associated with improved childbirth experiences in various settings; however, evidence from low-resource and culturally distinct contexts remains limited. Objective: To examine women’s experiences and satisfaction with midwifery-led care during childbirth in Thi-Qar, Iraq, and to compare it with physician-led care. Methods: A convergent parallel mixed-methods study was conducted among 150 postpartum women (≤6 weeks). Quantitative data were collected using the Mackey Childbirth Satisfaction Rating Scale (MCSRS) and analyzed with descriptive statistics, independent-samples t-tests, and Pearson/Spearman correlations. Qualitative data were obtained from 15–20 semi-structured interviews and underwent thematic analysis. Results: Mean item scores for midwifery-led care ranged from 2.76 to 3.15 (1–5 scale), indicating moderate satisfaction; maternal satisfaction scores ranged 2.89–3.04. No statistically significant correlation was observed between midwifery-led care scores and overall maternal satisfaction (Pearson r = –0.085; p = 0.298). Thematic analysis revealed strong communication and information provision but identified gaps in continuous emotional support, privacy, and pain management. Conclusion: While midwifery-led care was perceived positively in terms of communication, it did not consistently translate into higher maternal satisfaction in this setting. Interventions targeting continuous emotional support, pain relief, and birth environment may enhance satisfaction.